Sputum neutrophils as a biomarker in COPD: findings from the ECLIPSE study - Tal-Singer Ruth; Edwards Lisa; Singh Dave; Rennard Stephen (Respiratory Research, 2010)
Abstract Introduction The percentage of neutrophils in sputum are increased in COPD patients, and may therefore be a biomarker of airway inflammation. We studied the relationships between sputum neutrophils and FEV1, health status, exacerbation rates, systemic inflammation and emphysema, and long term variability at 1 year. Methods Sputum samples were obtained from 488 COPD patients within the ECLIPSE cohort. 359 samples were obtained at baseline, and 297 after 1 year. 168 subjects provided samples at both visits. Serum interleukin-6 (IL-6), IL-8, surfactant protein D and C-reactive protein levels were measured by immunoassays. Low-dose CT scans evaluated emphysema. Results Sputum neutrophil % increased with GOLD stage. There was a weak association between % sputum neutrophils and FEV1 % predicted (univariate r2 = 0.025 and 0.094 at baseline and year 1 respectively, p < 0.05 after multivariate regression). Similar weak but significant associations were observed between neutrophil % and health status measured using the St Georges Respiratory Questionairre. There were no associations between neutrophils and exacerbation rates or emphysema. Associations between sputum neutrophils and systemic biomarkers were non-significant or similarly weak. The mean change over 1 year in neutrophil % was an increase of 3.5%. Conclusions Sputum neutrophil measurements in COPD are associated weakly with FEV1 % predicted and health status. Sputum neutrophil measurements were dissociated from exacerbation rates, emphysema and systemic inflammation.